Trend Korupsi Kepala Daerah; Studi pada Pemerintahan Daerah di Sumatera Utara - Harits, Muhammad; Gozali, Vito Ammar; Oktaviani, Nur Harfi; Agustina, Karina Dwi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2019)
Corruption is an act that is disserve to society and the state because it will disturb the stability of the country. There is no country in the world that is immune from corruption because the state which is a very large public organization in which there are many parties who have different personal interests but the levels are different from one country to another. corruption that involving state officials including regional heads are often in indonesia. One of the highest level of corruption in Indonesia is North Sumatera. This study uses qualitative methods and descriptive analysis on secondary data. Data are collected through literature review on primary and secondary sources. The result showed that bad work environment, organizational culture that has existed for a long time, and personal interst causes a corruption tradition in North Sumatera.